Nashville noir : a novel - Bain, Donald (New York : New American Library, 2010)
Jessica Fletcher knows that creativity must be nurtured. So when a young lady from Cabot Cove shows promise as a singer and songwriter, Jessica and a local citizens committee send Cyndi on a scholarship trip to Nashville, Tennessee, where she can benefit from professional instruction. Only weeks later, Cabot Cove is shocked to hear of the cold-blooded murder of a brash country music publisher -- by the young talent Cyndi! And as Cyndi's mother begs Jessica to help her daughter, Jess heads to the country music capital of the world to help the wayward starlet. Jessica finds that the murdered man was no country gentleman, with a list of ex-wives, cheated partners, swindled singers, and stolen songs that has Jessica swinging to-and-fro in the search for a killer. And if she can't uncover the culprit soon, Jessica knows that poor Cyndi will never get the chance for an encore...
"An Obsidian mystery."
"Based on the Universal television series created by Peter S. Fischer, Richard Levinson & William Link."
Keywords: Women detectives -- Fiction; Women novelists -- Fiction; Women singers -- Fiction; Music publishers -- Crimes against -- Fiction; Mystery